Dazzled by the light: the impact of light pollution from ships on seabirds at Tristan da Cunha. (27th August 2021) - Ryan, Peter G; Ryan, E Molly; Glass, James P
Abstract : Most of the millions of burrow-nesting petrels that breed at Tristan da Cunha are susceptible to light pollution. On dark, misty nights, petrels become disoriented by artificial lights, mainly from ships. From 2013 to 2021 at least 1 823 petrels were recorded coming aboard vessels fishing for rock lobsters. Despite limited deck lighting, bird strikes occurred on 13% of fishing nights, with 65% of birds recorded on seven nights (<1%). Strikes occurred more often in spring and autumn than in summer, probably as a result of seabird breeding phenology and seasonal weather patterns. At least 70 birds were killed (4% of those reported from the ships), mainly prions Pachyptila spp. and storm petrels of family Oceanitidae. These represent minimum estimates, because not all birds are detected by the ships' crews. All vessels operating close to seabird breeding islands at night should be required to black out all but the most essential lights.